PELATIHAN INTERVAL INTENSITAS TINGGI LEBIH EFEKTIF MENURUNKAN PERSENTASE LEMAK TUBUH DIBANDINGKAN PELATIHAN KONTINYU SUBMAKSIMAL PADA SISWA SMAN 4 TASIKMALAYA - Dita Permatasari; Susy Purnawati; Muh. Ali Imron; Bagus Komang Satriyasa; Luh Made Indah Sri Handari Adiputra; Sugijanto - (Program Studi Magister Fisiologi Keolahragaan, Fakultas Kedokteran, Universitas Udayana, 2017)
Background: Body fat percentage can be increased with an unbalanced state between energy intake with energy output. Individuals who are overweight and obesity requires an exercise program to reduce the percentage of body fat. Objective: This study aims to prove the high intensity interval training to more effectively reduce the percentage of body fat than continuous submaximal training in class XI student of SMAN 4 Tasikmalaya. Method: This experimental (pre and post-test control group design) involved 40 samples who overweight and obese individuals were divided into 2 groups with randomization. Group I received high intensity interval training and group II received continuous submaximal training. Treatment was given for 8 weeks, the frequency of 3 times/week, duration of 60 minutes/session. Result: The results of a study reported decreased body fat percentage of the average of 40.47±3.27% to after the training 36.3±2.88% in group I and from average 41.93±2.93% to after training 38.93±3.13% in group II. Different test body fat percentage before and after high intensity interval training using paired sample t-test showed p=0.000 (p<0.05). Different test body fat percentage before and after continuous submaximal training using paired sample t-test showed p=0.000 (p<0.05). Statistical analysis of body fat percentage difference after high intensity interval training and continuous submaximal training using independent sample t-test showed p=0.009 (p<0.05). Decreasing body fat percentage of high intensity interval training is 4.17±2% while 3±2.25% in continuous submaximal training. Conclusion: High intensity interval training is more effective than continuous submaximal training in reducing body fat percentage in class XI student of SMAN 4 Tasikmalaya.